Studying distributed cognition of simulation-based team training with DiCoT. Issue 3 (3rd March 2016) - Rybing, Jonas; Nilsson, Heléne; Jonson, Carl-Oscar; Bang, Magnus
Abstract: Health care organizations employ simulation - based team training (SBTT) to improve skill, communication and coordination in a broad range of critical care contexts. Quantitative approaches, such as team performance measurements, are predominantly used to measure SBTTs effectiveness. However, a practical evaluation method that examines how this approach supports cognition and teamwork is missing. We have applied Distributed Cognition for Teamwork (DiCoT), a method for analysing cognition and collaboration aspects of work settings, with the purpose of assessing the methodology's usefulness for evaluating SBTTs. In a case study, we observed and analysed four Emergo Train System® simulation exercises where medical professionals trained emergency response routines. The study suggests that DiCoT is an applicable and learnable tool for determining key distributed cognition attributes of SBTTs that are of importance for the simulation validity of training environments. Moreover, we discuss and exemplify how DiCoT supports design of SBTTs with a focus on transfer and validity characteristics. Practitioner Summary: In this study, we have evaluated a method to assess simulation-based team training environments from a cognitive ergonomics perspective. Using a case study, we analysed Distributed Cognition for Teamwork (DiCoT) by applying it to the Emergo Train System®. We conclude that DiCoT is useful for SBTT evaluation and simulator (re)design.